2008
DOI: 10.2166/wst.2008.819
|View full text |Cite
|
Sign up to set email alerts
|

Weighing environmental advantages and disadvantages of advanced wastewater treatment of micro-pollutants using environmental life cycle assessment

Abstract: Much research and development effort is directed towards advances in municipal wastewater treatment aiming at reducing the effluent content of micro-pollutants and pathogens. The objective is to further reduce the eco-toxicity, hormone effects and pathogenic effects of the effluent. Such further polishing of the effluent, however, involves an environmental trade-off: the reduction in eco-toxicity, hormone effects, etc. will happen at the expense of increased resource- and energy consumption. Obviously, at some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 0 publications
4
43
0
Order By: Relevance
“…It is worth pointing out that the pilot study could directly feed the LCA with first-hand data. This makes the present work particularly coherent and closes the gap in previous investigations [11,12].…”
Section: Introductionsupporting
confidence: 89%
“…It is worth pointing out that the pilot study could directly feed the LCA with first-hand data. This makes the present work particularly coherent and closes the gap in previous investigations [11,12].…”
Section: Introductionsupporting
confidence: 89%
“…Qiting and Xiheng, 1988;Zwiener and Frimmel, 2004;Ravina et al, 2002;Kiffmeyer, 2003;Ternes et al, 2003;Watkinson et al, 2007;Strä ssle, 2007;Isidori et al, 2007), filtration (Schrö der, 2002;Drewes et al, 2002;Heberer and Feldmann, 2005), application of powdered charcoal (Metzger et al, 2005;Nowotny et al, 2007) and the use of man-made wetlands (Matamoros and Bayona, 2006). Reviews on the advantages and disadvantages of the different technologies are available (Schulte-Oehlmann et al, 2007;Wenzel et al, 2008;Ternes and Joss, 2006). However, all of these technologies have more or less specific shortcomings:…”
Section: Advanced Effluent Treatmentmentioning
confidence: 99%
“…None of the technologies can remove all of the compounds (Qiting and Xiheng, 1988;Ravina et al, 2002;Schrö der, 2002;Ternes et al, 2003;Wenzel et al, 2008). Will they work for future compounds?…”
Section: Advanced Effluent Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be problematic when the sludges are subsequently applied to land since these contaminants can threaten crop yields, long term soil quality, wildlife and eventually human health [23][24][25]. Research has shown that these compounds can be treated using advanced oxidation processes, but improvements in effluent quality comes at the considerable expense of increased materials and energy consumption [26]. For this reason, alternative processes are sought that can target these compounds for treatment in a more efficient and effective manner.…”
Section: Introductionmentioning
confidence: 99%